2009
DOI: 10.1037/a0013689
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Domain-Specific Self-Esteem: A Meta-Analysis

Abstract: This meta-analysis examines gender differences in 10 specific domains of self-esteem across 115 studies, including 428 effect sizes and 32,486 individuals. In a mixed-effects analysis, men scored significantly higher than women on physical appearance (d ϭ 0.35), athletic (d ϭ 0.41), personal self (d ϭ 0.28), and self-satisfaction self-esteem (d ϭ 0.33). Women scored higher than men on behavioral conduct (d ϭ Ϫ0.17) and moral-ethical self-esteem (d ϭ Ϫ0.38). The gender difference in physical appearance self-est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
192
10
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(240 citation statements)
references
References 70 publications
29
192
10
9
Order By: Relevance
“…First, even though the SPPA shows favorable psychometric properties (Harter, 1988;Wichstrøm, 1995) and is one of the most used measures of domain-specific self-esteem among adolescents (Gentile et al, 2009;Huang, 2010), slightly different results may have been obtained with a different self-esteem scale. For instance, Huang (2010) showed that mean developmental trajectories of global self-esteem differed significantly according to the scale used to assess self-esteem.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 3 more Smart Citations
“…First, even though the SPPA shows favorable psychometric properties (Harter, 1988;Wichstrøm, 1995) and is one of the most used measures of domain-specific self-esteem among adolescents (Gentile et al, 2009;Huang, 2010), slightly different results may have been obtained with a different self-esteem scale. For instance, Huang (2010) showed that mean developmental trajectories of global self-esteem differed significantly according to the scale used to assess self-esteem.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Global and domain-specific self-esteem was assessed by a revised version of the Self-Perception Profile for Adolescents (SPPA) (SPPA; Harter, 1988), which is one of the most used measures of domain-specific self-esteem among adolescents (Gentile et al, 2009;Huang, 2010). The original version is a 45-item self-report scale consisting of nine subscales.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gentile, Grabe, Dolan-Pascoe, and Wells (2009 ) have published a meta-analysis on domain-specifi c sex diff erences regarding self-esteem, but these results may not be automatically be generalized to self-esteem contingencies. found that compared with men, women's self-worth depends more on approval, appearance, academics, and family support, which fi ts with a rather social profi le, in line with fi ndings by Josephs, Markus, and Tafarodi (1992 ).…”
mentioning
confidence: 99%